Integrating Co-Creation and Open Innovation for Sustainable Value Creation: Evidence from Muslim-Friendly Restaurants in Tokyo - Fadillah, Ikhbal; Ismoyowati, Dyah; Falah, Mohammad Affan Fajar; Tsujimoto, Masaharu (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2025)
The growing presence of Muslim residents and visitors in Japan has increased the need for food services that align with Muslim-friendly expectations. However, limited empirical research examines how co-creation and open innovation contribute to sustainable business performance in this niche sector. This study explores these dynamics by analysing insights from five Muslim-friendly restaurants in Tokyo and survey responses from 57 Muslim consumers. The findings show that consumer involvement in open innovation activities meaningfully enhances several dimensions of sustainability, including financial performance, environmental responsibility, and social value creation, thereby strengthening trust and loyalty. Despite these positive outcomes, restaurants continue to face operational constraints—particularly certification challenges and the costs associated with providing fully Muslim-friendly offerings. The study suggests refining the DART (Dialogue, Access, Risk–Benefit Assessment, and Transparency) framework to reflect co-creation practices in minority-market food services better. Overall, the results confirm that open innovation significantly drives sustainable business outcomes (β = 0.675, p < 0.05) and provide strategic guidance for Muslim-friendly restaurants seeking to expand their market reach and enhance long-term sustainability.